2006
DOI: 10.1126/science.1126038
|View full text |Cite
|
Sign up to set email alerts
|

CO/FT Regulatory Module Controls Timing of Flowering and Seasonal Growth Cessation in Trees

Abstract: Forest trees display a perennial growth behavior characterized by a multiple-year delay in flowering and, in temperate regions, an annual cycling between growth and dormancy. We show here that the CO/FT regulatory module, which controls flowering time in response to variations in daylength in annual plants, controls flowering in aspen trees. Unexpectedly, however, it also controls the short-day-induced growth cessation and bud set occurring in the fall. This regulatory mechanism can explain the ecogenetic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
946
4
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 918 publications
(1,009 citation statements)
references
References 21 publications
34
946
4
2
Order By: Relevance
“…The protein product of FT acts as the florigenic component, that is translocated to Arabidopsis buds (Corbesier et al, 2007). This conclusion is supported by translocation from leaves to buds of an analogous protein encoded by Hd3a, a rice ortholog of FT, which appears to be the florigen operating in that crop (Tamaki et al, 2007), and the aspen ortholog, PtFT1, which along with CONSTANS was demonstrated to regulate the timing of flowering and growth cessation of Populus trichocarpa (Bohlenius et al, 2006). Once translocated to buds, the protein product of FT is thought to combine with the bZIP transcription factor (FD) protein to activate transcription of floral identity genes, such as APETALA1 (AP1) to begin floral expression (Abe et al, 2005;Wigge et al, 2005).…”
Section: Tl Davenportmentioning
confidence: 90%
“…The protein product of FT acts as the florigenic component, that is translocated to Arabidopsis buds (Corbesier et al, 2007). This conclusion is supported by translocation from leaves to buds of an analogous protein encoded by Hd3a, a rice ortholog of FT, which appears to be the florigen operating in that crop (Tamaki et al, 2007), and the aspen ortholog, PtFT1, which along with CONSTANS was demonstrated to regulate the timing of flowering and growth cessation of Populus trichocarpa (Bohlenius et al, 2006). Once translocated to buds, the protein product of FT is thought to combine with the bZIP transcription factor (FD) protein to activate transcription of floral identity genes, such as APETALA1 (AP1) to begin floral expression (Abe et al, 2005;Wigge et al, 2005).…”
Section: Tl Davenportmentioning
confidence: 90%
“…In balsam poplar, our analyses implicate FRI in the response to local selection at different latitudes, probably reflecting a role of FRI in the temperaturesensitive timing of seasonal development. Because floweringtime homologs in Populus can affect a range of developmental traits, including flowering and bud dormancy (Böhlenius et al 2006;Ingvarsson et al 2008;Lagercrantz 2009;Ma et al 2010), the link between allelic variation in FRI and variation in specific phenotypes in poplar awaits further study.…”
Section: Molecular Adaptation Of Phenology Network Genesmentioning
confidence: 99%
“…In contrast to the very high levels of segregating variation in Populus LFY, Arabidopsis LFY harbors low diversity consistent with a recent selective sweep . The protease-encoding EARLY BOLTING IN SHORT DAYS (EBS) that regulates the transition from juvenile to reproductive maturity in Populus through transcriptional control of FT (Böhlenius et al 2006) also showed an excess of north-south differentiation.…”
Section: Molecular Adaptation Of Phenology Network Genesmentioning
confidence: 99%
See 2 more Smart Citations